MATERNAL RISK ECLAMPSIA - Maradiegue Méndez, Eduardo (2015)
A retrospective study of 31 eclamptic patients, giving an incidence of 2 eclamptic 0.6 per 1,000 births, including 4 patients died giving a specific maternal mortality rate of 1,600 per 10,000 live births is presented. 96.8% were patients without prenatal care. The variety antepartum was more frequent with an incidence of 83.9%. Maternal mortality was higher in patients older than 30 years (37%) all the mothers who died had spontaneous labor, the causes of death were renal failure (two cases) and hepatic rupture cerebral edema (one case ed one).